2018
DOI: 10.1002/ajpa.23615
|View full text |Cite
|
Sign up to set email alerts
|

Of mice and men (and women): Comment on Peacock et al., 2018

Abstract: Of mice and men (and women): Comment on Peacock et al., 2018We read with interest the recent paper by Peacock et al. (2018) reporting the effects of wheel running exercise on femoral crosssectional geometry and other mechanical properties in three inbred strains of mice. We agree that the general issues addressed in the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…possibly the strain 3 wheel access interaction. Results of our reanalysis are summarized in Tables 2 and 3, which are comparable to Ruff et al's (2018) Figure 2a and 2c which is unsurprising, given previously observed shape differences in MM mice relative to unaffected mice (Middleton et al, 2010).…”
Section: Ruff Et Al Reanalyze Our Data For Estimates Of Bending Rigisupporting
confidence: 75%
See 2 more Smart Citations
“…possibly the strain 3 wheel access interaction. Results of our reanalysis are summarized in Tables 2 and 3, which are comparable to Ruff et al's (2018) Figure 2a and 2c which is unsurprising, given previously observed shape differences in MM mice relative to unaffected mice (Middleton et al, 2010).…”
Section: Ruff Et Al Reanalyze Our Data For Estimates Of Bending Rigisupporting
confidence: 75%
“…Although we were not able to exactly reproduce the p values in Ruff et al's (2018) Figure 1, even using a factorial ANCOVA on our own data, we agree that log-transformed femoral length predicted by log-transformed body mass are credibly different between strains. The posterior intervals of differences between MM and C57 or C3H have about 99% posterior probability of not including zero, with no credible effect of wheel access (Table 1).…”
mentioning
confidence: 52%
See 1 more Smart Citation